Enzyme activity analysis of CYP2C18 with exon 5 skipped - ZHU-GE Jian; YU Ying-nian (Acta Pharmacologica Sinica, 2016)
AIM: To study the enzyme activity of CYP2C18 variant with exon 5 skipped. METHODS: A full length CYP2C18 cDNA X1 and an exon 5 skipped variant CYP2C18 X2 were separately subcloned into mammalian expression vector pREP9 to transfect HepG2 cells. The expression of CYP2C18 mRNA in transgenic cells and human liver tissues were determined by RT-PCR. The enzyme activity of CYP2C18 to oxidate tolbutamide in postmitochondrial supernate (S9) fraction was determined by HPLC. The cytotoxicity of ifosfamide to transgenic cells was evaluated by MTT test. RESULTS: HepG2-CYP2C18 X1 cells showed strong expression of the full length CYP2C18 mRNA. On the other hand, HepG2-CYP2C18 X2 cells had only infinitesimal expression of the exon-skipped CYP2C18 as well as the full length CYP2C18, while non-transfected HepG2 cell only demonstrated an infinitesimal expression of the full length CYP2C18. The expression of CYP2C18 exons 2 to 7 was also analyzed by RT-PCR in 7 extratumoral liver tissues. Among them, 3 samples expressed only wild type mRNA, whereas 4 samples expressed both wild type and alternative splicing products. The tolbutamide hydroxylase activity of CYP2C18 was tested, and it was shown that HepG2-2C18 X1 cells had higher enzyme activity than those of HepG2-2C18 X2 and HepG2 cells. The relative survival of HepG2-CYP2C18 X1 cells was lower than that of HepG2 cells with 1, 2, and 4 mmol/L ifosfamide treatments. In contrast, the relative survival of HepG2-CYP2C18 X2 cell was the same as that of HepG2 cell in 0.5 and 1 mmol/L of ifosfamide, but lower than that of HepG2 cell in 2 and 4 mmol/L of ifosfamide. CONCLUSION: CYP2C18 X1 could metabolize tolbutamide and ifosfamide efficiently. The exon 5-skipped CYP2C18 X2 could not metabolize tolbutamide, and could not metabolize ifosfamide effectively at low concentrations.